Situation Report: Romania, 4 September 1984 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Visitors and History Underscore Autonomy / by Anneli Maier Honecker's Visit / by Patrick Moore Forty Years After: Regime Promises and Performance / by Vladimir Socor Romania in Los Angeles: Medals for the Maverick / by Anneli Maier Summer Recreation Facilities Again under Fire / by Crisula Stefanescu